Оценка урожаев гречихи разного вида и уровня с учетом тепловых ресурсов почв в Сумской области - Кирнасовская, Н.В. (Культура народов Причерноморья, 2013)
Выполнена количественная оценка микроклиматической изменчивости показателей
тепловых ресурсов почвы пахотного слоя с учетом разного механического состава в Сумской области.
На основе физико-статистической модели "Климат – урожай" рассматривается количественная
оценка урожаев грчихи разного вида и уровня для условий открытого ровного места на
среднесуглинистых почвах, а также под влияние климата различных почв данной территории.
Ключевые слова: гречиха, микроклимат почв, потенциальный урожай, действительно-возможный
урожай. Виконана кількісна оцінка мікрокліматичної мінливості показників теплових ресурсів ґрунтів
орного шару з урахуванням різного механічного складу у Сумській області. На основі фізико-
статистичної моделі «Клімат-урожай" розглядається кількісна оцінка врожаїв гречки різного виду та
рівня для умов відкритого рівного місця на середньосуглинкових ґрунтах, а також під впливом клімату
різних ґрунтів даної території.
Ключові слова: гречка, мікроклімат ґрунтів, потенційний врожай, дійсно-можливий врожай. The quantitative assessment of microclimatic variability of the topsoil’s thermal resources with the
different texture in the Sumy region is made. Based on the physic-statistical model "Climate - harvest" the
quantitative assessment of the different buckwheat sorts and levels for the conditions of the open flat place on
the smooth medium loamy soils, as well as under the climate influence of different soils of the area is considered.
Basing on the microclimate assessment of the buckwheat yield of different sorts and levels concidering the
thermal resources of the soils of different texture we can state that currently growing buckwheat in the working
environment in the Sumy region, the efficiency of the use of phased array of this culture is: in the first
agroclimatic area of the region at the level 0,4% in the east of the second agroclimatic area of the region at
0,8% in the west and south-west of the same area at 0,6-0,4%. Therefore, there remains a substantial reserve for
reaching 1-1,5% use efficiency due to rational culture’s placement, the proper selection of varieties, strict
technologies’ maintenance and accounting microclimatic characteristics of the area.
Keywords: buckwheat, microclimate of the soils, potential yield, actual-possible yield.